2008
DOI: 10.1016/j.lingua.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Control without a subject

Abstract: The aim of this paper is to develop a representation of control that does not require a PRO-subject. I first analyse obligatory control using a de-compositional analysis of u-roles, according to which u-roles are divided into two selectional requirements. The resulting theory makes the same predictions as one based on PRO, yet avoids dependence on this ill-defined empty category. I then concentrate on Icelandic, tackling agreement phenomena in infinitival clauses. Again no PRO is necessary to cater for the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The results for complement control, where neither cue could affect participants’ interpretations, corroborate the long-established obligatory-control classification of this construction. Controlled complements are selected by a control verb and the interpretation of the understood subject in that complement is constrained structurally (see Williams 1980; Manzini 1983; Landau 2000, 2013; Hornstein 2001; Janke 2007, 2008). Note also that there is no ambiguity with respect to the structure of object-controlled complements: the complement, selected by the head, is sister to that head.…”
Section: Discussionmentioning
confidence: 99%
“…The results for complement control, where neither cue could affect participants’ interpretations, corroborate the long-established obligatory-control classification of this construction. Controlled complements are selected by a control verb and the interpretation of the understood subject in that complement is constrained structurally (see Williams 1980; Manzini 1983; Landau 2000, 2013; Hornstein 2001; Janke 2007, 2008). Note also that there is no ambiguity with respect to the structure of object-controlled complements: the complement, selected by the head, is sister to that head.…”
Section: Discussionmentioning
confidence: 99%
“… Not all generative analyses of control posit a syntactic element in the controlled position (e.g., Brame , Evers , Janke ; functional control in Lexical Functional Grammar, Bresnan , Asudeh , Falk ; Categorial Grammar, Dowty ; Conceptual Structure approaches, Jackendoff & Culicover ). Trivially, theories without (a counterpart of) PRO do not face any questions about the status of PRO's features.…”
mentioning
confidence: 99%
“…Perovic et al (2013a,b), for example, reported that reflexive binding caused no problems to HFA children classified as ALN (autism with normal language). Reflexive binding is a relation that does not incorporate movement and shares many other syntactic properties with obligatory control (see Manzini, 1983; Koster, 1987; Janke, 2008). …”
Section: Introductionmentioning
confidence: 99%